Capitalism and Christianity, American Style - Connolly, William E. (Duke University Press, 2008)
Frontmatter -- Contents -- Preface -- Introduction: The Spirit of Capitalism -- 1. The Volatility of Capitalism -- 2. The Evangelical-Capitalist Resonance Machine -- 3. Between Science and Faith -- 4. Is Eco-egalitarian Capitalism Possible? -- 5. Christianity, Capitalism, and the Tragic -- Notes -- Index